2002
DOI: 10.1007/s00066-002-0886-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberration in Peripheral Lymphocytes and Doses to the Active Bone Marrow in Radiotherapy of Prostate Cancer

Abstract: The yield of dicentric aberrations for prostate cancer patients correlated closely with the mean bone marrow dose albeit the induction of dicentrics occurred in mature T lymphocytes most of which were probably in transit through the irradiated volumes. Therefore, the observed relationship between dicentrics and mean bone marrow doses are indirect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…The whole organism response could be due to tissue damage either in the tumor or the surrounding healthy tissues, which would induce a defensive physiologic response, e.g., a cytokine-induced inflammatory response. Direct effects could result from a well-known response of cells to radiation where such cells carry within them evidence of the exposure, i.e., radiation-induced heritable damage [10], but also from direct exposure of the bone marrow [16]. Despite a difference of means, the t-test revealed no significant differences in the levels of radiation-induced apoptosis observed before and after the 3 weeks of radiation therapy.…”
Section: Does the Sensitivity Of The T-lymphocytes To Radiation-inducmentioning
confidence: 73%
“…The whole organism response could be due to tissue damage either in the tumor or the surrounding healthy tissues, which would induce a defensive physiologic response, e.g., a cytokine-induced inflammatory response. Direct effects could result from a well-known response of cells to radiation where such cells carry within them evidence of the exposure, i.e., radiation-induced heritable damage [10], but also from direct exposure of the bone marrow [16]. Despite a difference of means, the t-test revealed no significant differences in the levels of radiation-induced apoptosis observed before and after the 3 weeks of radiation therapy.…”
Section: Does the Sensitivity Of The T-lymphocytes To Radiation-inducmentioning
confidence: 73%
“…Several studies have examined chromosome aberrations in blood samples from patients undergoing fractionated radiotherapy. These studies, which have used conventional cytogenetics, fluorescence in situ hybridisation (FISH) or both, showed a dosedependent increase in the yields of aberrations, but with substantial interpatient variability [9][10][11]. The same variability in the rate of damage induced in lymphocytes during radiotherapy has been observed in other studies that used different measurements, such as premature chromosome condensation (PCC), micronuclei or c-H2AX foci [12][13][14].…”
mentioning
confidence: 71%
“…While the appearance of the inducible repair for cellular survival has been seen in vitro in a wide range of cell lines using single dose experiments [ a study by Gershkevitsh et al [35] has recently shown data for chromosome aberrations following prostate radiotherapy with fractionated treatments that has an appearance characteristic to the inducible repair effect. This does not appear for all the data sets shown in their study, but given the large variability of biological data it does suggest that inducible repair might appear for chromosome aberrations as well.…”
Section: Resultsmentioning
confidence: 99%